(untitled) (Bangladesh Journal of Plant Taxonomy, 2024)
An investigation was carried out from January to July 2021 to study the diversity of macrofungi from mangrove ecosystem of Sundarbans of Bangladesh. This paper deals with 7 newly recorded macrofungi found in Sundarbans of Bangladesh namely, Entoloma strictius (Peck) Sacc., Hexagonia hirta (P. Beauv.) Fr., Hexagonia tenuis (Hook.) Fr., Hexagonia nitida Durieu & Mont., Coriolopsis gallica (Fr.) Ryvarden, Pleurotus pulmonaris (Fr.) Quél., Trichaptum abietinum (Dicks.) Ryvarden. Detailed taxonomic description of the newly reported species with photographs are provided here. Bangladesh J. Plant Taxon. 31(2): 293-299, 2024 (December)